INTEGRATING FREELANCERS AND CONTRACTORS ORGANIZATIONAL STRATEGIES FOR THE FUTURE WORKFORCE - Ridhayantho, Muhamad (Penelitian dan Pengembangan Ilmu, 2024)
The role of freelancers and contractors in the modern workforce is increasingly significant, but their integration with the organization's strategic goals often faces challenges, especially in maintaining organizational culture. This research aims to identify effective strategies in aligning an organization's long-term goals with a flexible workforce, using an approach Systematic Literature Review (SLR) based on PRISMA guidelines. Analysis of the relevant literature revealed four main themes: strategic workforce planning, the challenges of cultural integration, the role of technology as a facilitator, and the importance of adaptive leadership. These results provide theoretical insights into hybrid workforce management as well as practical recommendations for organizations to create a cohesive workforce without compromising organizational values.